Cultivo do abacaxizeiro cv. Vitória em função de épocas de plantio e indução floral - Küster, Ivanildo Schmith (2015)
The Ananas comosus (L.) Merrill popularly known as pineapple, belongs to the Bromeliad family, it is widely consumed in Brazil and worldwide. The consumer market is increasingly demanding for quality products, therefore, due to increased production, producers should seek to raise the standard of quality for potentiating their marketing. The pineapple culture faces some problems in Brazil, one of them concerns fusarium, the principal pathogen is Fusarium guttiforme. Resistant varieties such as cv. Vitória, has become a solution. The natural flowering is another problem that must be avoided as it could result in serious losses for producers. Research worldwide is being made to improve fruit quality. In this context, they have developed two works: the first aimed to evaluate the quality of fruits of pineapple cv. Vitória in planting dates function and floral induction in the north of the Espírito Santo. The second, aimed to study the phenotypic correlation between "D" Leaf characteristics, physical and chemical fruit of pineapple cv. Vitória. The experimental design was randomized blocks, in split plot, with four replications. In the main plot, they were tested different planting dates, corresponding to july 15 and september 01, 2013. The subplots were tested different times of flower induction, corresponding to ages 8, 10, 12 months and natural. Each subplot consisted of 60 plants, being evaluated 30 working plants in the center of the plot. The variables analyzed were: length, width, leaf area, diameter, circumference, fresh weight of the fruit with crown and the crown, central cylinder diameter, pulp thickness, pulp yield, pulp volume, translucent area, soluble solids, acidity titratable, ratio, duration in days from planting to first harvest, artificial induction of commencement of cropping, harvesting, thermal time (ST) in days from planting to artificial induction ST in days of induction at the beginning of the harvest and ST in days from planting to first harvest. Considering all variables, planting in July with induction at eight months is the most suitable for the production of pineapple cv. Vitória in the north of the Espírito Santo. Length and width of the sheet "D" can be used as physical quality indicators of fruits of pineapple cv. Vitória, but it should not be done about the chemical quality. The acidity of the fruits of pineapple cv. Vitória tend to be less with increasing weight of the fruit. The weight of the fruit is not influenced by the weight of the crown, so marketing the fruit in natura can be done without prejudice to the final consumer.